2021
DOI: 10.3390/microorganisms9102141
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Characterization of Growth Inhibition against the Gut Pathogen of Potentially Probiotic Lactic Acid Bacteria Strains Isolated from Fermented Products

Abstract: Lactic acid bacteria (LAB) are probiotic candidates that may restore the balance of microbiota populations in intestinal microbial ecosystems by controlling pathogens and thereby promoting host health. The goal of this study was to isolate potential probiotic LAB strains and characterize their antimicrobial abilities against pathogens in intestinal microbiota. Among 54 LAB strains isolated from fermented products, five LAB strains (NSMJ15, NSMJ16, NSMJ23, NSMJ42, and NFFJ04) were selected as potential probioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 80 publications
0
13
1
Order By: Relevance
“…As a result, the number of LGG bacteria was decreased slightly to 5.86 ± 0.45 log CFU/mL at 90 min and 5.06 ± 0.12 log CFU/mL at 180 min of exposure compared to that of the control (6.22 ± 0.05 log CFU/mL). Contrastingly, in the study by Jung et al ( 10 ), exposure of the same strain to pH 2.5 medium without pepsin for 2 h showed a remarkable decrease in the number of the cells (7.00 ± 0.67 log CFU/mL) compared to that of the control (9.79 ± 0.20 log CFU/mL). Thus, the method for conducting acid tolerance tests must be standardized and optimized to enhance the accuracy of the test.…”
Section: Introductioncontrasting
confidence: 57%
“…As a result, the number of LGG bacteria was decreased slightly to 5.86 ± 0.45 log CFU/mL at 90 min and 5.06 ± 0.12 log CFU/mL at 180 min of exposure compared to that of the control (6.22 ± 0.05 log CFU/mL). Contrastingly, in the study by Jung et al ( 10 ), exposure of the same strain to pH 2.5 medium without pepsin for 2 h showed a remarkable decrease in the number of the cells (7.00 ± 0.67 log CFU/mL) compared to that of the control (9.79 ± 0.20 log CFU/mL). Thus, the method for conducting acid tolerance tests must be standardized and optimized to enhance the accuracy of the test.…”
Section: Introductioncontrasting
confidence: 57%
“…Lacticaseibacillus paracasei NSMJ56 was selected for use in this study based on its high acid tolerance identified in a previous study [ 16 ]. L .…”
Section: Methodsmentioning
confidence: 99%
“…Lactic acid bacteria (LAB) are a major group of probiotic microorganisms in both humans and animals and are being extensively investigated in studies on probiotics ( 1 4 ). Lacticaseibacillus paracasei (formerly “ Lactobacillus paracasei ”) strain NSMJ15 was isolated from makgeolli, a traditional Korean fermented liquor, and in vitro study showed its probiotic potential, in particular, its antimicrobial properties against gut pathogens ( 5 ). Here, we report the complete genome sequence of strain NSMJ15, which supports its characteristics as a potential probiotic candidate.…”
Section: Announcementmentioning
confidence: 99%
“…Strain NSMJ15 was first isolated by serial dilutions of a makgeolli suspension and plating onto MRS agar (Difco, USA) ( 5 ). For whole-genome sequencing, genomic DNA (gDNA) was extracted from strain NSMJ15 grown in MRS broth (Difco) at 30°C for 48 h using a Maxwell 16 DNA purification kit (Promega, USA).…”
Section: Announcementmentioning
confidence: 99%